THE PROBLEM OF WIVE NUSHUZ IN PREVENTING DOMESTIC VIOLENCE: IDEALITY AND REALITY - Faruq Thohir, Umar (JURNAL SIPAKALEBBI, 2022)
The thick patriarchal culture legitimizes men to always be superior figures over women. If there are men and women, then men are required to be leaders, women are as followers only. The categorization is always based on sex, not skills, eligibility, and leadership capabilities. This patriarchal culture also affects the formation of households, where women are required to continue to obey their husbands even though the husband's policies intimidate them. If the wife resists, the wife is considered nushuz to her husband. According to classical scholars, a nushuz wife may even be beaten based on Surah An-Nisa' [4]:34. This verse must be reinterpreted so that it does not become legitimacy for men to commit arbitrariness or even domestic violence. Through maudhui interpretations which are also combined with Indonesian legislation, this library article was compiled to gain a more comprehensive and gender responsive understanding. The research was conducted by understanding asbabun nuzul, munasabah verses and contextualizing them with current conditions. This study found that the concept of nushuz does not legalize violence against wives. The beating of a wife who commits nushuz contained in An-Nisa '(4): 34 must be interpreted as an act to teach lessons, not to hurt or even commit violence. The wife's nushuz act against her husband so that the husband is allowed to beat her is when the wife commits 'fahisyah mubayyinah' namely zina, according to An-Nisa' (4): 19. Even the beating of a husband to his wife until she is injured can be declared as a husband's nushuz to his wife, because based on Al-Baqarah (2): 229 the husband can actually divorce her in a good way, no need to do violence to his wife.